FT-Raman study of the (sub)picosecond dynamics in genomic DNA from plant tissues. Issue 5 (2009) - Muntean Muntean, Cristina M. Cristina M.; Bratu Bratu, Ioan Ioan
Abstract : In this paper the Raman total half bandwidths of eight genomic DNAs from leaf tissues [potato ( Solanum tuberosum L.), sword fern ( Nephrolepis exaltata L.), scopolia ( Scopolia carniolica Jacq.), redwood ( Sequoia sempervirens D. Don. Endl.), orchids ( Cymbidium × hybrida ), chrysanthemum ( Dendranthema grandiflora Ramat.) and common sundew ( Drosera rotundifolia L.)] have been measured. The dependencies of the total half bandwidths and of the global relaxation times, on DNA molecular subgroup structure and on the type of genomic plant DNA, are reported. It is shown that changes in the (sub)picosecond dynamics of molecular subgroups in genomic DNAs from leaf tissues can be monitored with Raman spectroscopy. Particularly, the Raman band parameters for the vibrations at 879 cm −1 (deoxyribose, dA), 1047 cm −1 (CO stretching C‒O‒P‒O‒C, dG), 1089 cm −1 (PO symmetric stretching of PO2 ‒ ), 1124 cm −1 (dA), 1272 cm −1 (dC, dG, dT), 1276 cm −1 (dC), 1455 cm −1 (deoxyribose, dA, dC, dT) and 1482 cm −1 (dG, dA) of genomic leaf tissues DNAs are presented. In our study, the full widths at half-maximum (FWHM) of the bands in genomic DNAs from leaf tissues are typically in the wavenumber range from 7.8 to 23.1 cm −1 . It can be observed that the molecular relaxation processes studied in this work, have a global relaxation time smaller than 1.36 ps and larger than 0.46 ps. The fastest and the slowest relaxation processes of different DNA structural subgroups, for several types of genomic DNA extracted from leaf tissue, have been analyzed. Particularly, the slowest dynamics corresponding to the vibration near 1272 cm −1 takes place in the case of DNA extracted from common sundew (global relaxation time 1.36 ps). A comparison between different time scales of the vibrational energy transfer processes, characterizing several DNA complexes, has been given. We have found that the bands at 879 cm −1 (deoxyribose, phosphodiester, dA) and 1455 cm −1 (deoxyribose, dA, dC, dT) are suitable for the study of dynamical behavior of molecular subgroups in genomic DNA extracted from leaf tissues. Specific molecular relaxation processes, depending on the type of genomic DNA extracted from leaf tissues has been observed.